Bauran Pemasaran Pupuk Organik Pupuk Organik pada Kelompok Tani Ternak Nandini Asri Desa Kelating Kecamatan Kerambitan, Tabanan - I MADE AGUS GIRI SANTOSA; DEWA GEDE AGUNG; I NYOMAN GEDE USTRIYANA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2013)
ABSTRACT Marketing Mix of Organic Fertilizer in a Stock Farmer Group of Nandini Asri at Kelating Village, Sub-district of Kerambitan Tabanan Marketing is a most important thing to be carried out by a company in its effort to create the market in order to get an opportunity to obtain the optimal profit and maintain the survival of the business. Any business in any field needs a support of marketing concept in the form of marketing mix covering product, price, promotion and place. In order to get the marketing objective, then those four elements should support each other. The aim of this research is to find out the marketing mix of organic fertilizer carried out by Stock Farmer Group of Nandini Asri in Tabanan and the constraints they are facing in applying the marketing mix. Marketing mix carried out by Stock Farmer Group of Nandini Asri is to produce three type of products which are planting media, decomposer (JMG) and organic fertilizer, to determine the selling price using cost pricing method, and to conduct the promotion using personal selling method, whereas for distribution channel used there are two channels. The main constraint faced in marketing mix is in the process of producing bio organic fertilizer and planting media in the rainy season which have a little obstacle in the drying process. Marketing mix which being carried out is preferable that stock farmer group to utilize more of existing technology. Key words: marketing, marketing mix, distribution channel, organic fertilizer.